Describing of elements IO field in a testing computer program - Igor V. Loshkov; Dmitriy I. Loshkov (Открытое образование (Москва))
A standard of describing the process of displaying interactive windows on a computer monitor, through which an output of questions and input of answers are implemented during computer testing, is presented in the article [11]. According to the proposed standard, the description of the process mentioned above is performed with a format line, containing element names, their parameters as well as grouping and auxiliary symbols. Program objects are described using elements of standard. The majority of objects create input and output windows on a computer monitor. The aim of our research was to develop a minimum possible set of elements of standard to perform mathematical and computer science testing.The choice of elements of the standard was conducted in parallel with the development and testing of the program that uses them. This approach made it possible to choose a sufficiently complete set of elements for testing in fields of study mentioned above. For the proposed elements, names were selected in such a way: firstly, they indicate their function and secondly, they coincide with the names of elements in other programming languages that are similar by function. Parameters, their names, their assignments and accepted values are proposed for the elements. The principle of name selection for the parameters was the same as for elements of the standard: the names should correspond to their assignments or coincide with names of similar parameters in other programming languages. The parameters define properties of objects. Particularly, while the elements of standard create windows, the parameters define object properties (location, size, appearance) and the sequence in which windows are created. All elements of standard, proposed in this article are composed in a table, the columns of which have names and functions of these elements. Inside the table, the elements of standard are grouped row by row into four sets: input elements, output elements, input-output elements, grouping elements. All parameters are collected into another table, columns of which have names, assignments and values of parameters. Elements, for which the parameters are intended, are indicated in whole lines inside of this table. After each table, the necessary explanations are given to some of its items.An eхаmple of use of the standard for creating an input window of polynomial coefficients is demonstrated at the end of this article. The example shows significant compactness and ease of recording. Moreover, the testing program, based on the elements of standard, proposed in this article was written on HTML, JavaScript, PHP program languages and allows to perform mathematical and computer science testing. The program is available on the website [20]. Students of Moscow State (National Research) University of Civil Engineering were tested frequently using this program.The composition of elements and their parameters proposed above is convenient and does not require the creators of test problems to have a high level knowledge of programming languages.